The arbitrage Pricing Theorem with Non Expected Utility Preferences - David Kelsey; Frank Milne (Queen's University, Department of Economics, 1992)
The arbitrage pricing theorem of finance shows that in certain circumstances the price of a financial asset may be written as a linear combination of the prices of certain market factors. This result is usually proved with von Neumann-Morgenstern preferences. In this paper we show that the result is robust in the sense that it will remain true if certain kinds of non expected utility preferences are used. We consider Machina preferences, the rank dependent model and non-additive subjective probabilities.
Keywords: 330